Economic Integration in Latin America: An Approach Through the Analysis of Bibliometric Indicators on Research Production - Malpica Zapata, William A.; Nauzan Ceballos, Víctor Hugo; Silva Rodríguez, Leidy Maritza (Organizations and Markets in Emerging Economies, 2022)
This article analyzes different bibliometric indicators on research papers which examine the issue of economic integration in the Latin American region. The documents have been obtained from the Scopus bibliographic database; a total of 564 papers published in the time span from 2000 to 2020 have been identified, processed, and analyzed using the open-source software Bibliometrix and Vos Viewer. The results achieved allow identifying elements such as volume and relevance in scientific publications by country, H-G-M index of researchers with the greatest impact, estimation of Lotka’s Law, the analysis of co-occurrence between keywords, the dynamics in publication of the main sources, and finally, the thematic evolution in the last two decades. The findings provide a better understanding of the research processes as well as a comprehensive analysis of authors, their impact and the relevant sources in the economic integration of Latin America.